The effect of sugammadex on postoperative cognitive function and recovery - Pişkin,Özcan (2016)
Abstract Background and objective: Sugammadex is the first selective relaxant binding agent. When compared with neostigmine, following sugammadex administration patients wake earlier and have shorter recovery times. In this study, we hypothesized that fast and clear awakening in patients undergoing general anesthesia has positive effects on cognitive functions in the early period after operation. Methods: Approved by the local ethical committee, 128 patients were enrolled in this randomized, prospective, controlled, double-blind study. Patients were allocated to either Sugammadex group (Group S) or the Neostigmine group (Group N). The primary outcome of the study was early postoperative cognitive recovery as measured by the Montreal Cognitive Assessment (MoCA) and Mini Mental State Examination (MMSE). After baseline assessment 12-24 h before the operation. After the operation, when the Modified Aldrete Recovery Score was ≥9 the MMSE and 1 h later the MoCA tests were repeated. Results: Although there was a reduction in MoCA and MMSE scores in both Group S and Group N between preoperative and postoperative scores, there was no statistically significant difference in the slopes (p > 0.05). The time to reach TOF 0.9 was 2.19 min in Group S and 6.47 min in Group N (p < 0.0001). Recovery time was 8.26 min in Group S and 16.93 min in Group N (p < 0.0001). Conclusion: We showed that the surgical procedure and/or accompanying anesthetic procedure may cause a temporary or permanent regression in cognitive function in the early postoperative period. However, better cognitive performance could not be proved in the Sugammadex compared to the Neostigmine.